AGILITY EXERCISE MODELS OF BADMINTON - Al Farisi, Muh Abd Harits (Program Pascasarjana Universitas Negeri Jakarta, 2018)
The purpose of this research and development is to produce a model of agility exercise on badminton. This research uses Research & Development (R & D) development method from Borg and Gall. Stages in this research and development are, at the stage: (1) needs analysis, (2) expert evaluation (initial product evaluation); (3) limited testing (small group trial); (4) main test (field testing), (5) Model effectiveness test. The effectiveness test uses the court agility test to determine the level of athletes fame in mastering the entire game area. Analysis of research data using T test with significance level 0,05. Data analysis is obtained by average value of test data agility as follows pretest: 505.40 and posttest 468.53. So this model of badminton agility training is effective in improving the agility of badminton athletes. Based on the results of the development can be concluded that: (1) With the model of agility exercise for badminton athletes can be developed and applied in the exercise at the club (2) With the agility training model for badminton athletes that have been developed, obtained evidence of this increase in the show on the test data pretest and posttest results of significant differences between before and after the treatment of the model.   Keywords: Development, Model, Agility, Badminton